IMAGE EQUALIZATION BASED ON SINGULAR VALUE DECOMPOSITION - Demirel, Hasan; Anbarjafari, Gholamreza; Jahromi, Mohammad N. Sabet (IEEE, 2008)
In this paper, a novel image equalization technique which is based on singular value decomposition (SVD) is proposed. The singular value matrix represents the intensity information of the given image and any change on the singular values change the intensity of the input image. The proposed technique converts the image into the SVD domain and after normalizing the singular value matrix it reconstructs the image in the spatial domain by using the updated singular value matrix. The technique is called the singular value equalization (SVE) and compared with the standard grayscale histogram equalization (GHE) method. The visual and quantitative results suggest that the proposed SVE method clearly outperforms the GHE method.
23rd International Symposium on Computer and Information Sciences (ISCIS) -- OCT 27-29, 2008 -- Istanbul, TURKEY
Keywords: Histogram Equalization